Coaching under pressure: A study of Olympic coaches - Olusoga, P.; Maynard, I.; Hays; Butt, J. (Journal of Sports Sciences, 2012)
The Olympic environment has been identified as particularly stressful and unlike any other in terms of the media attention and focus placed on the competition. While the potential negative consequences of stress for coaches and their athletes have been explored, relatively little is known about the factors underpinning successful Olympic coaching performance. We explored elite coaches' perceptions of the factors that enable them to coach in a stressful Olympic environment. Eight coaches from one of Great Britain's most successful Olympic teams (i.e. consistent medal winners in the previous three Olympics) were interviewed. Inductive content analysis indicated that psychological attributes (e.g. emotional control), preparation (e.g. strategic approach), and coping at the event (e.g. team support) were factors that coaches perceived as important for successful Olympic coaching. In addition, coaches offered specific suggestions for training and development. Key themes included coach interaction (e.g. mentoring, formalizing contact) and simulating Olympic pressure. These findings offer suggestions for the education of developing coaches on the pathway to elite sports coaching.